1993
DOI: 10.1159/000126424
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Adrenergic β-Receptor Stimulates Prolactin Release from Primary Cultured Pituitary Cells

Abstract: Prolactin release from primary cultured pituitary cells was investigated using a dynamic perifusion system. Although epinephrine (1 µmol/l) produced an elevation in the mean value of the prolactin concentration at the onset of the perifusion, the elevation was not statistically significant, and the overall effect of the epinephrine was to produce an inhibition of prolactin release. The α-and D2-receptors of the primary cultured cells were functionally removed by a pretreatment with phenoxybenzamine (0.1 or 1 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…24] and/or receptor-coupled activation of different G proteins [9,25,26]. These, in turn, could determine the direction of change in cytosolic calcium controlling PRL secretion [27], It is also possible that the steroid background may determine shifts in receptor specificity [28,29] or post receptor transduction coupling efficiency [30]. The data of the present study suggest that the steroid hormonal environment may dictate which receptors, signalling sys tems or ion channels are activated to transduce the differ ential response to DA.…”
Section: Discussionmentioning
confidence: 99%
“…24] and/or receptor-coupled activation of different G proteins [9,25,26]. These, in turn, could determine the direction of change in cytosolic calcium controlling PRL secretion [27], It is also possible that the steroid background may determine shifts in receptor specificity [28,29] or post receptor transduction coupling efficiency [30]. The data of the present study suggest that the steroid hormonal environment may dictate which receptors, signalling sys tems or ion channels are activated to transduce the differ ential response to DA.…”
Section: Discussionmentioning
confidence: 99%
“…dopamine, epinephrine, norepinephrine) or adrenergic agents directly alter anterior pituitary functions (Denef and Baes, 1982;Swartz and Moberg, 1986;Li, 1989;Shin and Barton, 1993;Colthorpe et al, 2000). In this research, we have observed small (up to approx.…”
Section: The Effect Of Gnrh α-And β-Adrenergic Agents On Prl Secretimentioning
confidence: 60%
“…Studies performed with pituitary cells derived from male rats have yielded discrepant results. Perkins et al (1985) did not observe any influence of β-adrenergic agonist (ISOP) on PRL release from pituitary cells, whereas Denef and Baes (1982) and Shin and Barton (1993) have demonstrated a stimulatory effect of the agonist on PRL secretion. Moreover, on the basis of pharmacological studies, Shin and Bar-ton (1993) concluded that β 2 -adrenergic receptors are implicated in the stimulation of PRL secretion and then suggested their presence within lactotrophs.…”
Section: The Effect Of Gnrh α-And β-Adrenergic Agents On Prl Secretimentioning
confidence: 84%
See 1 more Smart Citation
“…However, when dopamine stimulates or inhibits proiactin release in GH4ZR7 cells, it is clear that the dopamine should act on the short form of dopamine receptors since there is no other dopamine (or catecholamine) receptor in the GH4ZR7. A high concentration of dopamine can stimulate adrenergic P-receptors which transduct stimulatory action on proiactin release (Shin and Barton, 1993). Therefore, if other catecholamine receptors than dopamine are expressed in GH4ZR7 cells, there is a possibility that dopamine might activate other catecholamine receptors to stimulate proiactin release.…”
Section: Transduction Systemmentioning
confidence: 99%